Microwave-assisted catalytic pyrolysis of Dunaliella salina using different compound additives. (April 2020) - Chen, Chunxiang; Huang, Dengchang; Bu, Xiaoyan; Huang, Yuting; Tang, Jun; Guo, Chenxu; Yang, Shengxiong; Huang, Haozhong
Abstract: Microwave-assisted pyrolysis of Dunaliella salina was carried out. The effect of different types (mixtures of activated carbon (AC) with CaO and AC with Fe2 O3 ), different adding amounts (5, 10, 15, and 20%), and different mixing ratios (0:10, 3:7, 4:6, 5:5, 6:4, 7:3, and 10:0) of compound additives was evaluated, the results were compared with those of single additive and no additive groups. When the compound additive was a mixture of AC and CaO, the maximum weight loss rate ( R m ) and average weight loss rate ( R v ) of AC/CaO = 6:4 group at 20% addition were the largest, whereas the times corresponding to R m ( t m ) and weight stabilization ( t s ) were the smallest. The total weight loss ( M t ) of AC/CaO = 0:10 and 4:6 groups at 20% addition were the largest. When the compound additive was a mixture of AC and Fe2 O3, the R v and R m of AC/Fe2 O3  = 5:5 group at 15% addition were the largest, while the t s and t m were the smallest; The AC/CaO = 6:4 group at 20% addition was the best based on the M t of D. salina ; the AC/Fe2 O3  = 5:5 group at 15% addition was the best based on the R m, R v, t m, and t s of D. salina . Highlights: Activated carbon (AC) was mixed with CaO and Fe2 O3 as compound additive. The optimum amount and mixing ratio of two compound additives were obtained. AC/Fe2 O3 additive was synergied for pyrolysis rate of Dunaliella salina. Different mixing ratios and addition of AC/CaO show different effect on pyrolysis.